2009
DOI: 10.1002/ev.315
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge translation: Implications for evaluation

Abstract: Translation theory originates in the field of applied linguistics and communication. The term knowledge translation has been adopted in health and other fields to refer to the exchange, synthesis, and application of knowledge. The logic model is a circular or iterative loop among various knowledge translation actors (knowledge producers and users) with translation activities evolving and occurring at various stages. Successful knowledge translation depends on the engagement of the target audience, as well as u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
0
24
0
8
Order By: Relevance
“…The Canadian Institutes of Health Research demonstrated their interest by funding the International Collaboration on Complex Interventions (involving investigators from Canada, the United States, the United Kingdom, and Australia), which produced some of the key papers in these debates (7,16,31,34,36,55,62,65,67,94,96,98,110,120,128,129). This collaboration also enabled a partnership with the Centers for Disease Control and Prevention and the Prevention Research Centers with conferences in Chicago in 2009 (128), Montréal in 2010 (27), and Toronto in 2011 to advance theories and methods.…”
Section: The Complex Interventionmentioning
confidence: 99%
“…The Canadian Institutes of Health Research demonstrated their interest by funding the International Collaboration on Complex Interventions (involving investigators from Canada, the United States, the United Kingdom, and Australia), which produced some of the key papers in these debates (7,16,31,34,36,55,62,65,67,94,96,98,110,120,128,129). This collaboration also enabled a partnership with the Centers for Disease Control and Prevention and the Prevention Research Centers with conferences in Chicago in 2009 (128), Montréal in 2010 (27), and Toronto in 2011 to advance theories and methods.…”
Section: The Complex Interventionmentioning
confidence: 99%
“…This model implies that a sole emphasis on making information available and accessible (push) or only focusing on the stimulation of demand (pull) without then being able to satisfy that demand through an available distribution system (the infrastructure) is unlikely to effectively bridge research-practice gaps [33]. In this model, a key means for satisfying demand is setting up the conditions for existing distribution systems such as a healthcare or social services system, a professional association, or a network of businesses or community health outreach organizations to possess, deliver, and support the implementation and continued use of an innovation, often by partnering with stakeholders within the delivery system.…”
Section: A Market Oriented Push-pull Infrastructure Modelmentioning
confidence: 99%
“…Knowledge brokers are an emerging KT strategy and described as "persons or organizations that facilitate the creation, sharing, and use of knowledge" ( Meyer, 2010 , p. 119). Th e literature has described knowledge brokers as being responsible for a range of activities including linking researcher with knowledge users, appraising and disseminating relevant literature, identifying knowledge sources, and adapting knowledge for local contexts ( Conklin, Lusk, Harris, & Stolee, 2013 ;Dobbins et al, 2009 ;Lomas, 2007 ;Rivard et al, 2010 ). To explore this potential role and the evaluation strategies and activities to support knowledge translation, this study sought to answer the overarching question: How can evaluative inquiry be designed to facilitate knowledge translation?…”
Section: Evaluation and Ktmentioning
confidence: 99%